Solving Singed Product Cordial Labeling of Corona Products of Paths and the Third Power of Lemniscate Graphs - Atef Abd El-hay , Yasser Elmshtaye , A. Elrokh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
A graph